Some issues of ensuring the legality of regulator legal acts of executive bodies - Bilyalova, M.I.; Musilimova, K.S. (Bulletin of the Karaganda University “Law Series”, 2023)
This article discusses some issues on ensuring the legality of regulatory legal acts of the executive bodies of the Republic of Kazakhstan. In the context of the ongoing deep transformations in the socio-political life of the Republic of Kazakhstan, constitutional reform, radical modernization of the public administration system based on the principles of a “human-centered” model, the issues of legality of the executive bodies’ rulemaking activities, personifying the most numerous and branched governmental department, are of particular relevance. The affiliation of executive bodies’ normative legal acts, on the one hand, to the means of implementing the tasks and functions of executive power, and on the other hand, to one of the elements of the mechanism of legal regulation, determines the importance of scientific and theoretical research of their legal nature, the real achievement of the goals and objectives of public administration with strict observance of the principle of legality in the process of their preparation and publication. The concept of a regulatory legal act of executive bodies as a means of legal regulation in the field of public administration is analyzed; the most typical violations of the rule of law committed by subjects of executive power are investigated; measures are proposed to improve the organizational and legal mechanism for ensuring the requirements of legality to the rule-making activities of executive bodies, eliminating the consequences by canceling and (or) suspending illegal acts in an out of court and judicial order.